Takayasu arteritis: showed by a hypertensive crisis - Rita Rocha; Vânia Rodrigues; Adriana Santos Silva; Alcina Ponte (Sociedade Galega de Medicina Interna, 2020)
Introduction: Takayasu Arteritis (TA) is a primary granulomatous large vessel vasculitis, affecting predominantly young women 1. It mainly affects the aorta and its major branches. TA and the required immunosuppressive therapy cause considerable morbidity and mortality. 2 Early in the disease course, symptoms can be non-specific, leading to a difficult diagnosis. 3 Consequences of vascular stenosis, occlusions, and, less commonly, vascular dilation, account for the typical clinical presentation; the latter can sometimes lead to aneurysmal rupture or dissection. Though the importance of a comprehensive history and a thorough physical examination cannot be over-emphasized, clinical assessment is frequently inaccurate when evaluating disease activity, which may sometimes progress silently. Also the diagnostic modalities currently used are unsatisfactory. X-Ray angiography, the "gold standard" for TA diagnosis, can image luminal defects but does not detect changes of the vessel wall 4. The diagnosis of TA can be confirmed with histopathological examination; however, tissue from blood vessels is obtained only in the minority of patients requiring a surgical intervention. There are currently no specific biomarkers for diagnosing TA. Identifying disease activity in TA is challenging 3 Glucocorticosteroids are anchor drugs for this disease, like other vasculitis. Most cases in Japan respond with 0.3-0.5 mg/kg/day prednisolone, but we frequently found that some patients present with flare-ups during tapering of glucocorticosteroids. Since TAK mainly affects young women, side-effects of glucocorticosteroids, especially moon face, severely damage their quality of life. Immunosuppressive agents, including methotrexate, cyclosporine, cyclophosphamide, mycophenolate mofetil and taclolimus have been used for patients with TAK. Biological agents targeting tumor necrosis factor (TNF) have also been used for patients with TAK 5 This article aims the description of a clinical case of a serious appearance form of an uncommon disease, Takayasu's arteritis. Key-words: Takayasu Arteritis, Large vessel vasculitis, renal artery stenosis